Indigenous Georgian Wine-Associated Yeasts and Grape Cultivars to Edit the Wine Quality in a Precision Oenology Perspective - Vigentini, Ileana; Maghradze, David; Petrozziello, Maurizio; Bonello, Federica; Mezzapelle, Vito; Valdetara, Federica; Failla, Osvaldo; Foschino, Roberto (Frontiers in Microbiology, 2016)
In Georgia, one of the most ancient vine-growing environment, the homemade production of wine is still very popular in every rural family and spontaneous fermentation of must, without addition of chemical preservatives, is the norm. The present work investigated the yeast biodiversity in five Georgian areas (Guria, Imereti, Kakheti, Kartli, Ratcha-Lechkhumi) sampling grapes and wines from 22 different native cultivars, in 26 vineyards and 19 family cellars. One hundred and eighty-two isolates were ascribed to 15 different species by PCR-ITS and RFLP, and partial sequencing of D1/D2 domain 26S rDNA gene. Metschnikowia pulcherrima (F’ = 0.56, I’ = 0.32), Hanseniaspora gulliermondii (F’ = 0.49, I’ = 0.27) and Cryptococcus flavescens (F’ = 0.31, I’ = 0.11) were the dominant yeasts found on grapes, whereas Saccharomyces cerevisiae showed the highest prevalence into wine samples. Seventy four isolates with fermentative potential were screened for oenological traits such as ethanol production, resistance to SO2, and acetic acid, glycerol and H2S production. Three yeast strains (Kluyveromyces marxianus UMY207, S. cerevisiae UMY255, Torulaspora delbrueckii UMY196) were selected and separately inoculated in vinifications experiments at a Georgian cellar. Musts were prepared from healthy grapes of local varieties, Goruli Mtsvane (white berry cultivar) and Saperavi (black berry cultivar). Physical (°Brix) and microbial analyses (plate counts) were performed to monitor the fermentative process. The isolation of indigenous S. cerevisiae yeasts beyond the inoculated strains indicated that a co-presence occurred during the vinification tests. Results from quantitative GC-FID analysis of volatile compounds revealed that the highest amount of fermentation flavours, such as 4-ethoxy-4-oxobutanoic acid (monoethyl succinate), 2-methylpropan-1-ol, ethyl 2-hydroxypropanoate and 2-phenylethanol, were significantly more produced in fermentation conducted in Saperavi variety inoculated with K. marxianus, whereas other aromatic compounds like 3-methylbutyl acetate, ethyl hexanoate and dihydrofuran-2(3H)-one (γ- butyrolactone) showed a higher content in Goruli Mtsvane variety samples fermented by S. cerevisiae. The selected yeast strains have proved to be promising for enhancing the flavor potential in low aromatic Georgian cultivars. This work intends to be a knowledge contribution for a precision oenology toward the strategic concept of “one grape variety-one yeast”.